KAJIAN TENTANG KOMPETENSI ABSOLUT PERADILAN TATA USAHA NEGARA DALAM MENYELESAIKAN SENGKETA KEPUTUSAN FIKTIF POSITIF - M Aschari; Francisca Romana Harjiyatni (Kajian Hukum, 2017)
This research has objectives: 1) To know the application of absolute competence in resolving fictive-positive  dispute based on Government Administration Act; 2) To know the obstacles and solutions in applying the absolute competence of the  Administrative Court in solving the fictive-postive e dispute based on the Government Administration Act. The results showed that; 1). The application of absolute competence of Administrative Court (PTUN) is regulated in Supreme Court Regulation (PERMA) Number 5 Year 2015 (hereinafter referred to as Supreme Court Regulation of Fictive-Positive  Procedural Law). The regulation still has many shortcomings and limitations, so the implementation of the settlement of fictive-positive dispute  has not been regulated.  It causes legal uncertainty because there are still multiple interpretations of judges in response to the regulation. 2). The most complex obstacles are the lack of specific, clear and conclusive implementation guidelines. Suggestion: it is necessary to harmonize the Acts  between the Government Administration Act  and the  Administrative Court Act